2021
DOI: 10.7150/ijms.60342
|View full text |Cite
|
Sign up to set email alerts
|

L-3-n-butylphthalide promotes restoration after an experimental animal model of intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a devastating type of stroke with high morbidity and mortality, and the effective therapies for ICH remain to be explored. L-3-n-butylphthalide (NBP) is widely used in the treatment of ischemic stroke. However, few studies evaluated the therapeutic effects of NBP on ICH. Therefore, the present study aims to evaluate the effects of NBP on ICH and its potential mechanism. The rats were randomly divided into sham-operated group, saline-treated (ICH + saline) group, and NBP-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…We confirmed that UBIAD1 is expressed in cerebral tissues, where it is found in neurons, astrocytes, and microglia. In agreement with previous studies [ 28 , 48 , 49 ], suppressed UBIAD1 levels due to cerebral I/R were noted in both in vivo and vitro models. The upregulated UBIAD1 levels prevented brain tissues and neuronal impairments by inhibiting ferroptosis and lipid peroxidation during cerebral I/R.…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that UBIAD1 is expressed in cerebral tissues, where it is found in neurons, astrocytes, and microglia. In agreement with previous studies [ 28 , 48 , 49 ], suppressed UBIAD1 levels due to cerebral I/R were noted in both in vivo and vitro models. The upregulated UBIAD1 levels prevented brain tissues and neuronal impairments by inhibiting ferroptosis and lipid peroxidation during cerebral I/R.…”
Section: Discussionsupporting
confidence: 93%
“…The neuronal cells after Nissl staining had a square shape. TUNEL staining showed reduced apoptotic cells (Pi et al, 2021). Ferroptosis is another type of cell death (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…NBP can diminish brain cell apoptosis, safeguard neuronal cells, and repair neurological function, primarily through the upregulation of UBIAD1 expression. However, there has been limited investigation into the therapeutic potential of this compound in experimental models of hemorrhagic stroke (Pi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%